Pistachio green hull pectin: Optimization of microwave-assisted extraction and evaluation of its physicochemical, structural and functional properties. (15th January 2019) - Kazemi, Milad; Khodaiyan, Faramarz; Labbafi, Mohsen; Saeid Hosseini, Seyed; Hojjati, Mohammad
Highlights: Pistachio green hull was selected for pectin extraction optimization. 18.13 ± 0.53% of pectin were obtained under optimum extraction condition. DE of pectin extracted in optimum point was 12.1 ± 2.72%. HPLC analysis showed that galacturonic acid content was 66.0%. The average molecular weight of pectin extracted in optimum point was 1.659 kg/mol. Abstract: The optimal microwave-assisted extraction conditions of pistachio green hull (PGH) pectin (extraction yield of 18.13%) were in microwave power of 700 W, irradiation time of 165 s, and pH of 1.5. The physico-chemical, structural and functional properties of pectin was examined and the results showed that PGH pectin under optimum conditions was low methoxyl (about 12.1%) with molecular weight of 1.659 kg/mol, emulsifying activity of 58.3%, total phenolic content of 18.18 mg GalAE/g pectin and good surface activity (46.23 and 49.75 mN/m at 0.1 and 0.5% w/v). Also, high performance liquid chromatography analysis illustrated that the pectin is including galacturonic acid (66.0%), arabinose (26.2%), galactose (3.7%), rhamnose (2.7%) and xylose (1.0%). In addition, 1 H NMR and FTIR spectrums confirmed the presence of pectin in obtained supenatnt. Surface morphology analysis and X-ray diffraction pattern showed that PGH pectin had a rough surface with crystalline structure.